Georgia - Thompson, Kathleen (Milwaukee, WI : Raintree Publishers, 1986)
Discusses the history, economy, culture, and future of Georgia. Also includes a state chronology, pertinent statistics, and maps.
"Photographs from Portrait of America programs."
"A Turner book."
4.5
5-8
Keywords: Georgia -- Juvenile literature; Georgia; Georgia